PENGARUH ORIENTASI KEWIRAUSAHAAN DAN DUKUNGAN INSTITUSIONAL TERHADAP AGRIPRENEURSHIP PISANG CAVENDISH DI PROVINSI BENGKULU - Doni Wahyu Ramadhan; Nola Windirah; Agung Trisusilo; Pandu Laksono (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Agripreneurship is part of entrepreneurship that relates to the agricultural sector. Agripreneurship plays a vital role in promoting rural economic growth through job creation and increasing farmers’ income. In Bengkulu Province, agripreneurship is carried out on cavendish bananas in Bajak II Village, Bengkulu Tengah Regency, and Karanganyar Village, Kepahiang Regency. The increase in cavendish banana agripreneurship in Bengkulu Province faces problems that make it difficult to market cavendish bananas in modern markets. Therefore, this research aims to measure the level of entrepreneurship orientation, institutional support, agripreneurship, and to see whether there is an influence of entrepreneurship orientation and institutional support on agripreneurship. The method used is TCR and Structural Equation Modeling Partial Least Square (SEM-PLS) with a sample of 67 respondents. The research results show that the level of entrepreneurship orientation, institutional support, and cavendish banana agripreneurship in Bengkulu Province is still low, especially in risk-taking and partnerships. The influence of entrepreneurship orientation and institutional support has a significant impact on the agripreneurship of cavendish banana farmers in Bengkulu Province.